Theoretical Framework for Facilitating Young Musicians’ Learning of Expressive Performance - Meissner, Henrique (Frontiers in Psychology, 2021)
Since communication and expression are central aspects of music performance it is important to develop a systematic pedagogy of teaching children and teenagers expressiveness. Although research has been growing in this area a comprehensive literature review that unifies the different approaches to teaching young musicians expressiveness has been lacking. Therefore, the aim of this article is to provide an overview of literature related to teaching and learning of expressiveness from music psychology and music education research in order to build a new theoretical framework for teaching and learning expressive music performance in instrumental music lessons with children and teenagers. The article will start with a brief discussion of interpretation and expression in music performance, before providing an overview of studies that investigated teaching and learning of performance expression in instrumental music education with adults and children. On the foundation of this research a theoretical framework for dialogic teaching and learning of expressive music performance will be proposed and the rationale explained. Dialogic teaching can be useful for scaffolding young musicians’ learning of expressivity as open questions can stimulate thinking about the interpretation and may serve to connect musical ideas to the embodied experience of the learner. A “toolkit” for teaching and learning of expressiveness will be presented for practical application in music lessons. In addition, a theoretical model will be proposed to further our understanding of teaching and learning of expressive music performance as a multifaceted and interactive process that is embedded in the context of tutors’ and learners’ experiences and environment. Finally, implications of this framework and suggestions for future research will be discussed.